Application of interactive education in rural elderly diabetic patients with conversation map - Yingli, Zhang; Mingyun, Niu; Cuiqin, Zhang (International Journal of Advances in Medicine, 2021)
Background: The purpose of this study is to explore the effect of health education with conversation map on self-management ability of rural elderly diabetic patients. Methods: 60 rural elderly diabetic patients in endocrinology department of a 3A hospital from January to December in 2019 were selected as the research objects. According to the parity of the last two digits of the hospitalization number, the odd number was divided into the control group and the even number was divided into the experimental group. The control group was given traditional health education and interactive education with conversation map was added to the experimental group. After 3 months of intervention, fasting blood glucose, 2 hours postprandial blood glucose, glycosylated hemoglobin and self-management behavior of the two groups were observed. Results: The fasting blood glucose, 2h postprandial blood glucose, glycosylated hemoglobin and self-management ability of the experimental group were significantly better than those of the control group and the difference was statistically significant (p<0.05). Conclusions: The interactive education with conversation map can effectively improve the self-management ability of rural elderly diabetic patients, and then prevent the occurrence of diabetic complications.